Metabolic evaluation of patients with recurrent, multiple or bilateral renal stones in Jaffna - Rajendra, S. (Ceylon Medical Journal, 2020)
A comprehensive evaluation to identify metabolic abnormalities will help design management strategies for prevention of renal stone recurrences. The objective of this study is to identify the metabolic risk factors in a series of patients with recurrent, multiple or bilateral renal stone disease from the Northern Province, Sri Lanka.
Keywords: Metabolic evaluation; Nephrolithiasis; Recurrent and multiple; Bilateral renal stone formers)